Impact of IITA germplasm improvement on maize production in West and Central Africa - Manyong, Victor M.; Kling, J.; Mankinde, K.; Ajala, S.; Menkir, A. (2003)
The International Institute of Agriculture (IITA) is among the major suppliers of genetic materials to national agricultural research and extension systems in West and Central Africa for the development of improved maize varieties. This paper presents the results of a survey of the impact of germplasm from IITA on maize production and food security in 11 countries, which together contain over 90% of the area cultivated to maize in West and Central Africa. Between 1965 and 1998, the public sectors of these countries released a total of 186 varieties while the private sectors released 86 varieties. In the 1990s, IITA was the major source of maize germplasm used by these countries. Increased maize production from improved varieties was 2.6 million tonnes of grain in 1998, which could provide 2200 kcal per person per day to about 9.3 million people for one year. A total of 490 scientists were trained by IITA in maize research between 1970 and 1998.